2013
DOI: 10.1080/14681811.2012.709840
|View full text |Cite
|
Sign up to set email alerts
|

‘I make sure I am safe and I make sure I have myself in every way possible’: African-American youth perspectives on sexuality education

Abstract: High rates of youth pregnancy and STIs play a major role in the physical, mental, and emotional health of young people. Despite efforts to provide sexuality education through diverse channels, we know little about the ways in which young people perceive school- and community-based efforts to educate them about sexual health. Forty-eight African-American young people participated in six focus groups to discuss their sexuality education experiences. Three major themes emerged that highlight experiences and persp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…Students reported embarrassment and discomfort, particularly in mixed-sex SRE, 37 which impeded their engagement 38 as they feared humiliation in front of the class. 39 40 Young men reported that they were disruptive in SRE, 38 41–47 with some explaining their behaviour as a way of masking their anxiety. 47 It was observed that men are expected to be sexually knowledgeable and competent.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Students reported embarrassment and discomfort, particularly in mixed-sex SRE, 37 which impeded their engagement 38 as they feared humiliation in front of the class. 39 40 Young men reported that they were disruptive in SRE, 38 41–47 with some explaining their behaviour as a way of masking their anxiety. 47 It was observed that men are expected to be sexually knowledgeable and competent.…”
Section: Synthesismentioning
confidence: 99%
“… 51 Teachers themselves were commonly reported to be embarrassed and awkward delivering SRE. 37 39 40 42 48 50–56 …”
Section: Synthesismentioning
confidence: 99%
“…Recent Sex Education articles have deployed intersectionality in an effort to disrupt these oppressive conditions. Kimmel et al (2013) analyse the interactions of social locations and their impact on the access to and the content of sexuality education for African American youth. Utilising community-based participatory research, Kimmel and colleagues' (2013) article is one of a few to ask urban African American youth about their sexuality education experiences both inside and outside of school and to solicit their recommendations for improving sexuality education.…”
Section: Intersectionalitymentioning
confidence: 99%
“…This trust pattern is consistent with prior studies. Kimmel et al (), for example, conducted focus groups with 48 Black youths to discuss their sexual education experiences. They report that the school‐based sex education restricted the content covered and presented content in an uncomfortable way.…”
Section: Discussionmentioning
confidence: 99%